1995
DOI: 10.1084/jem.181.5.1661
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in mitochondrial potential constitutes an early irreversible step of programmed lymphocyte death in vivo.

Abstract: SummaryIn a number of experimental systems in which lymphocyte depletion was induced by apoptosisinducing manipulations, no apoptotic morphology and ladder-type DNA fragmentation were detected among freshly isolated peripheral lymphocytes ex vivo. Here we report that one alteration that can be detected among splenocytes stimulated with lymphocyte-depleting doses of dexamethasone (DEX) in vivo is a reduced uptake of 3,3'dihexyloxacarbocyanine iodide (DiOC6[3]), a fluorochrome which incorporates into cells depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
714
6
3

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,116 publications
(755 citation statements)
references
References 45 publications
29
714
6
3
Order By: Relevance
“…Bcl-2 on the endoplasmic reticulum membrane has been suggested to regulate intracellular calcium levels (Ba y et al, 1993;Lam et al, 1994;Marin et al, 1996), but its importance in anti-apoptotic activity depends on the unsolved question of whether Bcl-2 regulates calcium levels upstream of the caspase cascade. We recently showed that Bcl-2 and Bcl-x L , but not inhibitors of caspases, prevent apoptotic and necrotic stimuli-induced loss of mitochondrial membrane potential, whereas both Bcl-2 family proteins and caspase inhibitors prevent cell death (Zamzami et al, 1995;Shimizu et al, 1996b). The membrane potential loss leading to membrane permeability transition results in the release of an mitochondrial apoptogenic factor, AIF, which in turn, activates caspases as well as induces apoptotic change of the nucleus (Susin et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bcl-2 on the endoplasmic reticulum membrane has been suggested to regulate intracellular calcium levels (Ba y et al, 1993;Lam et al, 1994;Marin et al, 1996), but its importance in anti-apoptotic activity depends on the unsolved question of whether Bcl-2 regulates calcium levels upstream of the caspase cascade. We recently showed that Bcl-2 and Bcl-x L , but not inhibitors of caspases, prevent apoptotic and necrotic stimuli-induced loss of mitochondrial membrane potential, whereas both Bcl-2 family proteins and caspase inhibitors prevent cell death (Zamzami et al, 1995;Shimizu et al, 1996b). The membrane potential loss leading to membrane permeability transition results in the release of an mitochondrial apoptogenic factor, AIF, which in turn, activates caspases as well as induces apoptotic change of the nucleus (Susin et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 blocks the activation of caspases (Chinnaiyan et al, 1996;Shimizu et al, 1996a;Boulakia et al, 1996), probably by preventing the cell death-induced loss of mitochondrial membrane potential (Zamzami et al, 1995;Shimizu et al, 1996b). It has recently been described that Bcl-x L indirectly binds pro-FLICE (caspase-8) (Chinnaiyan et al, 1997), raising the possibility that Bcl-x L prevents the activation of caspases by sequestering pro-caspases.…”
Section: Introductionmentioning
confidence: 99%
“…The consequence of a partial IM permeabilization, which does not result in the release of matrix proteins but contribute to cell death, is that mitochondria lose their vital metabolic and redox functions (Zamzami et al, 1995;Metivier et al, 1998;Poncet et al, 2003). Mitochondrial permeabilization is therefore recognized as a crucial checkpoint in programmed cell death of both normal and cancer cells.…”
Section: Mitochondrial Membrane Permeabilization: the Central Event Omentioning
confidence: 99%
“…The cells were harvested, nuclei were stained with propidium iodide and the changes of fluorescence were measured by flow cytometry. 34 …”
Section: Measurement Of Mitochondrial Membrane Potentialmentioning
confidence: 99%